Effects of blanching on total phenolic contents determination in Parkia Speciosa / 'Asif Zainuddin - Zainuddin, 'Asif (Faculty of Applied Sciences, 2009)
Petai {Parkia speciosa@ petai beans) is a native plant of the Malay Peninsula, growing wild in lowland forests, often cultivated in Malay village. The pods taste like garlic and have a very strong odour. Petai are commonly cooked with "sambal tumis" or eaten raw with "sambal belacan". Before eat the petai, we must blanch the "petai" either by boiling or steaming. This project was carried out to determine effects of blanching on total phenolic contents in petai. Gallic acid was used as the standard thus the total phenolic content was expressed as mg GAE/g fresh sample. The total phenolic contents in raw is 0.800±0.011 mg GAE/g fresh sample . The selected blanching time for boiling method were 10, and 30 minutes and the total phenolic content were 0.541 ± 0.016 mg GAE/g fresh sample, and 0.459 ± 0.037 mg GAE/g fresh sample respectively. As for steaming method were also 10 and 30 minutes and the total phenolic content were 0.665 ± 0.007 mg GAE/g fresh sample and 0.459 ± 0.037 mg GAE/g fresh sample respectively. From this experiment, it was concluded that total phenolic content in Parkia speciosa was decreased as the blanching time was increased.